AGROWISATA NANAS BERBASIS EKOLOGI DI NGANCAR, KEDIRI - Parasita, Nitta; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Ngancar District is located around the slopes of Gunung Kelud and is in a strategic area with various kinds of potential, one of which is tourism potential and the potential for producing pineapples and processed pineapple products. However, there are currently no tourist attractions in Ngancar District that utilize the potential of natural resources and the environment, especially pineapple cultivation as a tourist attraction. Based on this, the concept and design of ecological-based pineapple agro-tourism was compiled by raising the problem of how to design pineapple-based agro-tourism as a means of recreation and education to accommodate the development of tourism potential in accordance with the potential of the environment. Five principles of ecological architecture are used as a concept in solving these problems. The concept of ecological architecture was developed based on the architectural programming method in the form of the activity patterns of farmers and tourists in Ngancar. The application of these five principles is grouped into three potentials, namely human potential, site potential, and natural potential. The concept is manifested in the design in the form of attractions, facilities, activities, the placement of the building mass, the shape and structure of the building, outdoor space, and utilities.